2015
DOI: 10.1016/j.molonc.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Personalised pathway analysis reveals association between DNA repair pathway dysregulation and chromosomal instability in sporadic breast cancer

Abstract: The Homologous Recombination (HR) pathway is crucial for the repair of DNA double-strand breaks (DSBs) generated during DNA replication. Defects in HR repair have been linked to the initiation and development of a wide variety of human malignancies, and exploited in chemical, radiological and targeted therapies. In this study, we performed a personalised pathway analysis independently for four large sporadic breast cancer cohorts to investigate the status of HR pathway dysregulation in individual sporadic brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 74 publications
(112 reference statements)
1
26
0
Order By: Relevance
“…Similarly, the number of DNA strand breaks and time required for their repair is significantly influenced by ageing (22,23). Double-strand DNA breaks can even participate to the loss of heterozygosity in the elderly and can be important for cancerogenesis (24,25). The total number of mutations acquired during ageing is extremely high, and robust genomic technologies demonstrated that 3,000-13,000 genes per genome can be affected by 5,000-50,000 mutations (26).…”
Section: Biological Background Of Ageing and Impact On Cancer Formationmentioning
confidence: 99%
“…Similarly, the number of DNA strand breaks and time required for their repair is significantly influenced by ageing (22,23). Double-strand DNA breaks can even participate to the loss of heterozygosity in the elderly and can be important for cancerogenesis (24,25). The total number of mutations acquired during ageing is extremely high, and robust genomic technologies demonstrated that 3,000-13,000 genes per genome can be affected by 5,000-50,000 mutations (26).…”
Section: Biological Background Of Ageing and Impact On Cancer Formationmentioning
confidence: 99%
“…A recent large study with pathway‐level analysis using hierarchical modeling across five cancers, including 11 Discovery, Biology, and Risk of Inherited Variants in Breast Cancer (DRIVE) genome‐wide association study (GWAS) datasets of 33,832 BC study subjects of European descent, did not find any specific risk‐associated SNPs in genes involved in NER, but the limited study power did allow the investigators to find an association with the overall genetic variation of the NER pathway . Other prior studies also investigated associations between SNPs in DNA repair pathway genes and BC risk, but these studies had relatively small sample sizes without a focus on the NER pathway, although they have some notable findings, such as XRCC3 and ERCC4 …”
Section: Introductionmentioning
confidence: 99%
“…16 Other prior studies also investigated associations between SNPs in DNA repair pathway genes and BC risk, but these studies had relatively small sample sizes without a focus on the NER pathway, although they have some notable findings, such as XRCC3 and ERCC4. [17][18][19][20][21][22][23][24] Therefore, we hypothesize that genetic variants in the NER pathway genes are associated with BC risk. To assess the role of functional SNPs of the NER pathway genes in the BC etiology, we performed a much larger meta-analysis of 14 previously published DRIVE GWAS datasets with 53,107 study subjects of European descent.…”
Section: Introductionmentioning
confidence: 99%
“…That suggested DNA replication stress can cause mitotic chromosome segregation error (CIN) in colon cancer [8]. Additionally, association between homologous recombination pathway (leading to replication stress and MIN) and CIN was identified in sporadic breast cancer, also supporting the notion that DNA metabolism defect leads to CIN [9].…”
Section: Introduction: Chromosome Instability (Cin) and Carcinogenesismentioning
confidence: 72%